2020
DOI: 10.1080/02678373.2020.1730481
|View full text |Cite
|
Sign up to set email alerts
|

What about me? The impact of employee change agents’ person-role fit on their job satisfaction during organisational change

Abstract: This is a repository copy of What about me? The impact of employee change agents' person-role fit on their job satisfaction during organisational change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
2
12
0
1
Order By: Relevance
“…Training of healthcare managers grounded in the understanding of medical consequences of decision-making and in a systematic scientific-like approach integrated with practice is shown to improve performance (Savage et al , 2018). Large-scale and systematic training in cascade models as the eHealth competence and Enhancing Value programmes of this case is important to build both organisational and individual capacity, a claim supported by several studies (Park and Lee, 2015; Augustsson et al , 2017; Kinnunen et al , 2019; Nielsen et al , 2020).…”
Section: Resultsmentioning
confidence: 90%
“…Training of healthcare managers grounded in the understanding of medical consequences of decision-making and in a systematic scientific-like approach integrated with practice is shown to improve performance (Savage et al , 2018). Large-scale and systematic training in cascade models as the eHealth competence and Enhancing Value programmes of this case is important to build both organisational and individual capacity, a claim supported by several studies (Park and Lee, 2015; Augustsson et al , 2017; Kinnunen et al , 2019; Nielsen et al , 2020).…”
Section: Resultsmentioning
confidence: 90%
“…Particularly, recent research (Salanova et al, 2020;Boulagouas et al, 2021) has shown the importance of the employees and their psychological factors in the change conduct, for instance, benefits of self-efficacy to work motivation, engagement and job satisfaction. Moreover, Nielsen et al (2020) have served to increase focus on management ingredients (i.e. participation, consultation, involvement, integration, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical framework and literature Person-role conflict and emotional exhaustion From the person-role perspective, resource loss can occur in the process of managing multiple roles at once (da Costa and Donald, 2003;Nielsen et al, 2020;Kahn et al, 1964). The COR theory states that the actual loss of or threat to resources is considered the primary mechanism leading to strain (Hobfoll et al, 2018), and several studies have shown that "emotional exhaustion" is a strain that is most responsive to the stressor (Boles et al, 1997;Karatepe and Aleshinloye, 2009;Wang et al, 2012).…”
Section: Exhausting Job Demand To Satisfymentioning
confidence: 99%